2023
DOI: 10.3354/esr01231
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive timing and putative mating behavior of the oceanic whitetip shark Carcharhinus longimanus in the eastern Bahamas

Abstract: Oceanic whitetip sharks Carcharhinus longimanus aggregate at Columbus Point, Cat Island, The Bahamas, in at least April and May. We show that signs of putative mating activity (i.e. bite wounds) on mature females, which dominate the aggregation, are exceedingly rare at that time, but may be more common in July. Male plasma testosterone concentrations also suggest that spermatogenesis occurs in April and May and copulation is underway or has just ended by July. We support these preliminary data with direct obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Indeed, oceanic predators can be attracted to foraging areas [94,95] where environmental characteristics (e.g., local bathymetry, ocean currents, on-shelf reef area [93]) enhance bottom-up processes [96,97] that attract potential prey [98,99]. For example, abundant pelagic teleost prey may attract wide-ranging oceanic whitetip sharks to CI in April-May, after which the high density of sharks may facilitate and coincide with mating in summer [21][22][23]. We encourage future research to clarify (1) temporal shifts in shark diversity, relative abundance, and demographic structure at apparent aggregation sites and (2) spatial variation in relative abundance between sites.…”
Section: Variable Species-specific Conservation Value Of Sites In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, oceanic predators can be attracted to foraging areas [94,95] where environmental characteristics (e.g., local bathymetry, ocean currents, on-shelf reef area [93]) enhance bottom-up processes [96,97] that attract potential prey [98,99]. For example, abundant pelagic teleost prey may attract wide-ranging oceanic whitetip sharks to CI in April-May, after which the high density of sharks may facilitate and coincide with mating in summer [21][22][23]. We encourage future research to clarify (1) temporal shifts in shark diversity, relative abundance, and demographic structure at apparent aggregation sites and (2) spatial variation in relative abundance between sites.…”
Section: Variable Species-specific Conservation Value Of Sites In The...mentioning
confidence: 99%
“…Some shelf-edge open-ocean habitats in the eastern Bahamas may serve as these habitats for wide-ranging oceanic and semi-pelagic sharks (as defined by [20]). For example, Critically Endangered (IUCN Red List of Threatened Species [15]) adult oceanic whitetip sharks aggregate off Columbus Point, Cat Island, The Bahamas (CI) in April-May, with at least 20% of individuals exhibiting multi-year site fidelity that may be motivated by abundant pelagic teleost prey in late spring [21] and/or mating in summer [22]. Satellite telemetry data revealed that oceanic whitetip sharks tagged at CI spent considerable time (24-100% of 31-245-day tag durations) within the Bahamian Exclusive Economic Zone (EEZ) [23], but sample size and inherent limitations of light-level based geolocation estimates precluded the fine-scale identification of high-use areas.…”
Section: Introductionmentioning
confidence: 99%